pMBRT: Principles and Design of Advanced Proton Radiotherapy Techniques - Xiaowa WANG; Ning DU; Lan WANG (Zhongguo yiliao qixie zazhi)
The development history of pMBRT, the biological role of minibeam, the mechanism of minibeam protection of tissues, the generation of minibeam (collimator method and magnetic focusing method), and the analysis of advantages and disadvantages of proton minibeam matrix arrays are introduced with advanced proton minibeam arrays (pMBRT). It is proposed that the combination of proton minibeam arrays and magnetic resonance fields can help to exploit the normal tissue protective function of pMBRT, and improve the precision of proton therapy.